5.1k views
3 votes
What conjecture can you make about the sum of firs 52 positive even numbers​

User Cooow
by
5.4k points

1 Answer

5 votes

Answer:

See Explanation

Explanation:

The question is incomplete. However, the available details is enough to work out a solution.

Considering the first even number: 2

In this case, n = 1

The sum of the first even term is 2.

Represent the sum as a product:


2 = 1 * 2

Considering the first two even numbers: 2 and 4

In this case, n = 2

The sum of the first two even terms is 6

Represent the sum as a product:


6 = 2 * 3

Considering the first three even numbers: 2, 4 and 6

In this case, n = 3

The sum of the first two even terms is 12

Represent the sum as a product:


12 = 3 * 4

Notice the pattern from n = 1 to 3


2 = 1 * 2 --- n = 1


6 = 2 * 3 --- n = 2


12 = 3 * 4 --- n = 3

------------------------------------

It follows that, the sum when represented as a product is:
n * (n + 1)

So, the sum of the first 52 even terms would be:


52 * (52 + 1)

Where n = 52


52 * (52 + 1) = 52 * 53


52 * (52 + 1) = 2756

Hence, the sum of the first 52 even terms is 52 * 53 or 2756

User Joseph Dattilo
by
5.8k points